HR analytics: A centralizing or decentralizing force? - Johannes Lehmann (University of Basel, Center of Business and Economics (WWZ), 2024)
This study empirically analyzes the relationship between the application of HR analytics and the assignment of decision-making authority in Swiss establishments. From a theoretical standpoint the direction of this relationship is ex-ante unclear as opposing forces are at work simultaneously. While HR analytics can reduce the local information advantage or even take over decision-making processes, acting as a centralizing force, it can also generate additional local information and dampen the hidden action problem, resulting in the decentralization of decision-making processes. The empirical results, relying on doubly robust ATE estimations, are in line with a decentralizing force of HR analytics. More precisely, a comprehensive measure of decision rights as well as operational and strategic decisions are more decentralized in establishments that apply HR analytics. Overall the findings suggest that Swiss establishment combine the use of HR analytics with employee empowerment and do not use it to create a dystopian work environment as feared by proponents of digital taylorism.
Keywords: L22; M12; M50; M54; 330; HR analytics; people analytics; decision-rights assignment; authority in organizations; doubly robust ATE estimation